1985
DOI: 10.1139/z85-324
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the eggshell of the fruit flies Dacus oleae and Ceratitis capitata (Diptera: Trypetidae)

Abstract: The eggshell of two fruit flies of economic importance has been studied by means of light and electron microscopy. The eggshell of the olive fruit fly, Dacus oleae, contains compact endochorion, whereas that of the Mediterranean fruit fly, Ceratitis capitata, exhibits a holey endochorionic layer. The eggshells of both species have an innermost chorionic layer which appears to be crystalline in substructure. The anterior pole in each case contains the micropylar canal but in addition it bears an elaborate "cup"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
32

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 0 publications
2
18
0
32
Order By: Relevance
“…The eggshell of B. oleae has a smooth chorion and is probably important in providing air to the developing embryos inside the fruit, as is known to be the case in other insect eggs (Hinton, 1981). The anterior and posterior poles that were photographed in living embryos in this study were described previously by Margaritis (1985) and Mouzaki and Margaritis (1991). The results of the present study were in agreement with their results by showing the anterior pole as inverted and cup-shaped.…”
Section: Discussionsupporting
confidence: 92%
“…The eggshell of B. oleae has a smooth chorion and is probably important in providing air to the developing embryos inside the fruit, as is known to be the case in other insect eggs (Hinton, 1981). The anterior and posterior poles that were photographed in living embryos in this study were described previously by Margaritis (1985) and Mouzaki and Margaritis (1991). The results of the present study were in agreement with their results by showing the anterior pole as inverted and cup-shaped.…”
Section: Discussionsupporting
confidence: 92%
“…Murillo and Jirón (1994) found that A. obliqua showed greater oxygen demand by depositing their eggs in a way that the respiratory appendages remain outside of the fruit. However, Margaritis (1985) believes that species such as A. serpentina and C. capitata can oviposit in greater depth due to an air chamber in eggs, which would not require immediately atmospheric oxygen. This discussion could explain oviposition of A. fraterculus and C. capitata (Table 1), since C. capitata oviposited deeper, when compared to A. fraterculus, except for guava fruit.…”
Section: Discussionmentioning
confidence: 99%
“…7, the exochorion (ex), the endochorionic sub-layers [outer endochorion (oe), pillars (p) and inner endochorion (ie)], the innermost chorionic layer (ICL) and the thick vitelline membrane (vm) are all highly enriched in gold particles (bPxd proteins), strongly indicating the essential biological significance and contribution of the bPxd peroxidase in the B. oleae chorion physiology. Interestingly, it was previously reported for B. oleae species, through an in situ cytochemistry approach, that, beyond the chorionic layers, the vitelline membrane also contains a strong H 2 O 2 -regulated peroxidase activity (Margaritis, 1985a). The strong immunoreactivity of the rabbit anti-rAePO polyclonal antibody with the 54 kDa chorionic component (Fig.…”
Section: Discussionmentioning
confidence: 78%